Trust - Díaz, Hernán, 1973- (Riverhead Books, 2022)
"An award-winning writer of absorbing, sophisticated fiction delivers a stylish and propulsive novel rooted in early 20th century New York, about wealth and talent, trust and intimacy, truth and perception. In glamorous 1920s New York City, two characters of sophisticated taste come together. One is a legendary Wall Street tycoon; the other, the brilliant daughter of penniless aristocrats. Steeped in affluence and grandeur, their marriage excites gossip and allows a continued ascent--all at a moment when the country is undergoing a great transformation. This is the story at the center of Harold Vanner's novel Bonds, which everyone in 1938 New York seems to have read. But it isn't the only version. Provocative, propulsive, and repeatedly surprising, Hernan Diaz's TRUST puts the story of these characters into conversation with the "the truth"--and in tension with the life and perspective of an outsider immersed in the mystery of a competing account. The result is an overarching novel that becomes more exhilarating and profound with each new layer and revelation, engaging the reader in a treasure hunt for the truth that confronts the reality-warping gravitational pull of money, and how power often manipulates facts"--